Melatonin normalizes clinical and biochemical parameters of mild inflammation in diet-induced metabolic syndrome in rats - Cano Barquilla, Pilar (2014)
Fil: Cano Barquilla, Pilar. Universidad Complutense. Facultad de Medicina. Departamento de Bioquímica y Biología Molecular III; España